Challenges in Managing a Moderate Burn with Suspected Mild Inhalation Injury in a Resource-Limited Setting: A Case Report - David Herryanto; Nugroho Muji Pamungkas (International Medical Journal Corp. Ltd, 2025)
Introduction: Burn injuries complicated by inhalation injury present a significant management challenge, associated with increased morbidity and mortality. This challenge is amplified in resource-limited settings where gold-standard diagnostic tools, such as fiberoptic bronchoscopy, are often unavailable. Case Illustration: We present the case of a 43-year-old male smoker with a history of asthma who sustained 24.5% Total Body Surface Area (TBSA) second-degree burns to the face, bilateral forearms, and lower legs following a gas cylinder explosion. Clinical findings upon admission, including hoarseness and singed nasal hairs, were highly suspicious for a mild inhalation injury. His hospital course was further complicated by newly diagnosed Stage 2 hypertension, prediabetes, and bronchopneumonia identified on the initial chest radiograph. Discussion: The diagnosis of inhalation injury was established on clinical grounds, necessitating close observation in an intensive care setting rather than immediate intubation. The patient's management involved aggressive fluid resuscitation guided by the Parkland formula, meticulous wound care with topical antimicrobials, and a coordinated multidisciplinary approach to address his complex respiratory status and multiple comorbidities. This case underscores the efficacy of relying on strong clinical judgment and collaborative care to navigate complex clinical scenarios. Conclusion: This case demonstrates that successful outcomes for complex burn patients with suspected inhalation injury are achievable in regional hospitals through a high index of suspicion, aggressive supportive care, and a robust multidisciplinary team, even in the absence of advanced diagnostic modalities.